Transition metal- and solvent-free double hydroboration of nitriles. Issue 4 (31st January 2020) - Bedi, Deepika; Brar, Aneelman; Findlater, Michael
Abstract : An operationally convenient, room temperature synthesis of N, N -diborylated amines via hydroboration of nitriles using a commercially available catalyst. Abstract : A highly efficient, room temperature double hydroboration of nitriles under transition metal-free and solvent-free conditions is reported. Sodium triethylborohydride is used as a catalyst and yields up to 99% are disclosed. Mechanistic studies reveal the reaction proceeds in a stepwise manner with initial formation of a boryl-imine which undergoes a second hydroboration to afford a diborylated amine product.